2016
DOI: 10.2337/dc15-2418
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of All-Cause Mortality and Cardiovascular Disease in Association With Prior History of Hypoglycemia Among Patients With Type 1 Diabetes

Abstract: OBJECTIVEThis study investigated the effects of severe hypoglycemia on risks of all-cause mortality and cardiovascular disease (CVD) incidence in patients with type 1 diabetes mellitus (T1DM). RESEARCH DESIGN AND METHODSTwo nested case-control studies with age-and sex-matched control subjects and using the time-density sampling method were performed separately within a cohort of 10,411 patients with T1DM in Taiwan. The study enrolled 564 nonsurvivors and 1,615 control subjects as well as 743 CVD case subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 32 publications
2
38
0
2
Order By: Relevance
“…In a Taiwanese cohort study, the adjusted HR was 1.57 for diabetes with a history of SH as compared to those without [58]. Another study reported an elevated risk of fall associated with a history of hypoglycemia (adjusted HR, 1.36; 95% CI, 1.13 to 1.65) [59].…”
Section: Adverse Outcomes Of Severe Hypoglycemiamentioning
confidence: 99%
“…In a Taiwanese cohort study, the adjusted HR was 1.57 for diabetes with a history of SH as compared to those without [58]. Another study reported an elevated risk of fall associated with a history of hypoglycemia (adjusted HR, 1.36; 95% CI, 1.13 to 1.65) [59].…”
Section: Adverse Outcomes Of Severe Hypoglycemiamentioning
confidence: 99%
“…Severe hypoglycemia is recognized as one of the strongest predictors of macrovascular events in patients with type 1 diabetes and type 2 diabetes, which was also noted by studies from Taiwan and Japan. The increased risk of cardiovascular diseases is associated with long‐term hypoglycemia, either as a result of weight gain related to defensive food intake, or through activation of the sympathoadrenal response.…”
Section: Challenges With Basal Insulin Therapy In Asiamentioning
confidence: 85%
“…70 The authors conclud ed that repeated severe hypoglycemic events can lead to higher risk of mortality and cardiovascu lar disease. 70 Furthermore, a study among Swed ish patients with type 1 diabetes found that those with prior severe hypoglycemic events present ed an increased risk of mortality after a cardio vascular event.…”
mentioning
confidence: 99%
“…70 The authors conclud ed that repeated severe hypoglycemic events can lead to higher risk of mortality and cardiovascu lar disease. 70 Furthermore, a study among Swed ish patients with type 1 diabetes found that those with prior severe hypoglycemic events present ed an increased risk of mortality after a cardio vascular event. 71 Unfortunately, the mechanism of hypoglyce miarelated all cause mortality and cardiovas cular events is not fully known; it is only sus pected that it is due to sympathetic adrenal ac tivations, prolonged cardiac repolarization, and increased cardiac arrhythmia risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation